Peptides/receptors signaling during plant fertilization - Yu, Tian-Ying; Xu, Chun-Xia; Li, Wen-Jia; Wang, Bo (Frontiers in Plant Science, 2022)
Double fertilization is a unique and particularly complicated process for the generation alternation of angiosperms. Sperm cells of angiosperms lose the motility compared with that of gymnosperms. The sperm cells are passively carried and transported by the pollen tube for a long journey before targeting the ovule. Two sperm cells are released at the cleft between the egg and the central cell and fused with two female gametes to produce a zygote and endosperm, respectively, to accomplish the so-called double fertilization process. In this process, extensive communication and interaction occur between the male (pollen or pollen tube) and the female (ovule). It is suggested that small peptides and receptor kinases play critical roles in orchestrating this cell-cell communication. Here, we illuminate the understanding of phases in the process, such as pollen-stigma recognition, the hydration and germination of pollen grains, the growth, guidance, and rupture of tubes, the release of sperm cells, and the fusion of gametes, by reviewing increasing data recently. The roles of peptides and receptor kinases in signaling mechanisms underlying cell-cell communication were focused on, and directions of future studies were perspected in this review.